Aspects of Cloud Environment Protection in Higher Education. Microsoft Technologies - Pavlova, Elitsa (Research Papers, 2025)
The transition to cloud infrastructure presents significant cybersecurity challenges for higher education institutions. This report examines the role of three leading Microsoft solutions – Microsoft Defender, Microsoft Sentinel, and Azure Security Centre – in providing comprehensive IT protection. It analyses their application, benefits, and opportunities for integration into academic environments. The study highlights the need for a unified cloud cybersecurity strategy, security policy enforcement, and IT team training to ensure data integrity and privacy in the higher education sector.
Keywords: Cloud environment; Cybersecurity; Micrоsoft Defender (software); Microsoft Sentinel (software); Azure Security Centre (software); Higher education institutions